(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2021)
This article examines and compares the representation of ethnic minority lead investigators in the television crime series, Tatort Hamburg (ARD, 2008-2012 season), Cherif (France 2, 2013-2019), Last Panthers (Canal+, 2015), and Dogs of Berlin (Netflix, 2018). It suggests a typology of the figure of the ethnic minority detective based on representational patterns shared by the series and other literary and television narratives, which is discussed and contextualized within the ideological and commercial limitations of French and German television cultures. The last section assesses the series’ potential to depict ‘postmigrant societies’ founded on and influenced by social plurality and former and ongoing migration movements. In so doing, the study highlights role of typologies and narrative tropes in the portrayal of ethnic minorities in crime television and insists, despite the shortcomings of some series’ representational strategies, on the value of figures of identification for minority and majority audiences that attest to a shifting understanding of ‘us’ and ‘others’ in contemporary European societies.